Gaetano Perusini: The Forgotten Neuroscientist Behind "Alzheimer's" Disease. (June 2023) - Pellegrini, Francesco; Rosso, Mattia; Chu, Duong T.
Alzheimer's disease (AD) is a neurodegenerative disorder characterized by cognitive and behavioral impairment with social and occupational impacts. This form of dementia is being increasingly studied, and its prevalence is expected to rise in the near future. Gaetano Perusini, a neuroscientist in the Alzheimer's laboratory, has played a major clinical and pathological role in the earlier study of Alzheimer's disease. This article summarizes his role in the discovery of the disease, which should be fairly named Alzheimer-Perusini disease.